2020
DOI: 10.1186/s13104-020-05241-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic and the lockdown on invasive meningococcal disease

Abstract: Objective: Few data are available on the association between SARS-CoV-2 and secondary bacterial infections. Such an association was described for flu and invasive meningococcal disease (IMD). We aimed exploring such a correlation between COVID-19 and IMD as well as the impact of the lockdown on IMD. Results: We compared IMD cases received at the French National Reference Centre for meningococci and Haemophilus influenzae that are sent as part of the mandatory reporting of IMD. We compared these data during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 16 publications
1
46
0
2
Order By: Relevance
“…MenY is also expressed in cc11, cc32, and cc41/44 clonal complex backgrounds that are more frequently associated with other capsular groups. Interestingly, comparison of IMD cases during a 2-month lockdown period in 2020 and the same periods of 2018 and 2019 in France found significant decrease in all IMD cases from prior years, and seemed to mainly involve IMD cases due to groups B and C and W, but not IMD due to group Y and other groups or nongroupable isolates [ 11 ]. The MenY genotypes had not changed in 2020 and were cc23 [ 11 ].…”
Section: Minor N Meningitidis Capsular Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…MenY is also expressed in cc11, cc32, and cc41/44 clonal complex backgrounds that are more frequently associated with other capsular groups. Interestingly, comparison of IMD cases during a 2-month lockdown period in 2020 and the same periods of 2018 and 2019 in France found significant decrease in all IMD cases from prior years, and seemed to mainly involve IMD cases due to groups B and C and W, but not IMD due to group Y and other groups or nongroupable isolates [ 11 ]. The MenY genotypes had not changed in 2020 and were cc23 [ 11 ].…”
Section: Minor N Meningitidis Capsular Groupsmentioning
confidence: 99%
“…Interestingly, comparison of IMD cases during a 2-month lockdown period in 2020 and the same periods of 2018 and 2019 in France found significant decrease in all IMD cases from prior years, and seemed to mainly involve IMD cases due to groups B and C and W, but not IMD due to group Y and other groups or nongroupable isolates [ 11 ]. The MenY genotypes had not changed in 2020 and were cc23 [ 11 ]. The observed IMD decreased mainly in the highly transmissible and hyperinvasive isolates belonging to cc11.…”
Section: Minor N Meningitidis Capsular Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that the incidence of specific pathogen infections such as influenza viruses, respiratory syncytial virus, meningococcus, and pneumococcus was reduced in many countries. 18 , 19 , 20 , 21 Australia reported a concurrent lower frequency of respiratory syncytial virus detection and admission to hospital for bronchiolitis in 2020 as compared with preceding years. 19 In this country, despite schools reopening, a 99.4% reduction was reported in influenza detection following Australian public health measures.…”
Section: Shift Of Paradigmmentioning
confidence: 97%
“… 18 These data suggest that the epidemiology of these infectious diseases may change in an unpredictable manner in the coming months and years, requiring close and active surveillance. 18 , 19 , 20 , 21 …”
Section: Shift Of Paradigmmentioning
confidence: 99%